Tumor-Associated Tertiary Lymphoid Structures: Gene-Expression Profiling and Their Bioengineering - Zhu, Genyuan; Falahat, Rana; Wang, Kui; Mailloux, Adam; Artzi, Natalie; Mulé, James J. (Frontiers in Immunology, 2017)
Tertiary lymphoid structures (TLSs) have been identified in the parenchyma and/or in the peripheral margins of human solid tumors. Uncovering the functional nature of these structures is the subject of much intensive investigation. Studies have shown a direct correlation of the presence of human tumor-localized TLS and better patient outcome (e.g., increase in overall survival) in certain solid tumor histologies, but not all. We had identified a tumor-derived immune gene-expression signature, encoding 12 distinct chemokines, which could reliably identify the presence of TLSs, of different degrees, in various human solid tumors. We are focused on understanding the influence of TLSs on the tumor microenvironment and leveraging this understanding to both manipulate the antitumor immune response and potentially enhance immunotherapy applications. Moreover, as not all human solid tumors show the presence of these lymphoid structures, we are embarking on bioengineering approaches to design and build “designer” TLSs to address, and potentially overcome, an unmet medical need in cancer patients whose tumors lack such lymphoid structures.